An Individualised Homoeopathic Approach to Chronic Atopic Dermatitis: A Case Report - Mukherjee, Suranjana; Sahoo, Sanjib (Homœopathic Links, 2024)
Atopic dermatitis is a chronic inflammatory skin disease affecting about one-fifth of all individuals during their lifetime. It has substantial impact on the quality of life of the affected individual. Not only patient is affected by the social stigma of a visible skin condition but also the characteristic itch-scratch cycle often leads to skin trauma and significant sleep disruption. Though there is multitude of treatment options in modern medicine, the recurrence, and adverse effects of medications cannot be ruled out. Therefore, an alternative approach is required. The case presented here reported with the complaint of severe generalised itching eruptions for the last 8 years with a history of atopy. After thorough evaluation from the clinical and homoeopathic standpoint, a single homoeopathic medicine Arsenicum iodatum was prescribed in different potencies at different timepoints as the symptomatology corresponds. Following the administration of individualised homoeopathic (IH) medicine, there was gradual improvement in the case with disappearance of skin lesions which was also evaluated through reduction in SCORing Atopic Dermatitis and Dermatology Life Quality Index scores. During the treatment, old symptoms also reappeared indicating improvement in accordance with Hering's law of cure and Kent's 11th observation. The modified Naranjo criteria score after the treatment course was 10 which exclusively shows positive causal attribution of the IH in this case.
Keywords: homoeopathy; atopic dermatitis; Arsenicum iodatum; SCORAD; DLQI